Analysis of the Communication Style of Habib Husein Ja'far Al-Hadar's Da'wah - Nova Ardiana (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
This paper discusses how to use Youtube as a means for da'wah. As the times get more advanced and technology becomes more sophisticated a da'i's challenge is to think of ways how the teachings of religion that want to be shared can be accessed by many people. So the authors are interested in researching about the digital propaganda Habib Husein Ja'far Al Hadar, an Indonesian citizen of Arab descent in between his busy life as a writer making the Youtube channel Jeda Nulis as a container and tool to be used to spread the teachings of Islam. Bring friends to discuss from various backgrounds and different backgrounds. The author found several important points of what Habib Husein Ja'far Al Hadar had conveyed over the past year. First, Islam is a religion to convey good news and Islam is a religion of love. Second, Islam teaches its people to tolerate fellow human beings. Third, convey the truth with good character. Fourth, jihad starts from simple things.